EQUILIBRIUM CONDITION OF WEDGE-TYPE COUNTERPART WITHOUT EXTERNAL STRESSES - Y. V. Vasilevich; O. M. Ostrikov (Наука и техника)
An equilibrium condition on a wedge-type counterpart without external stresses and with approaches of dislocation mezoscopic model has been derived in the paper. The paper describes balanced length dependencies of the wedge-type counterpart on forces that resist to motion of twinning dislocations.